Circulating levels of vitamin D3 and leptin in lean infertile women with polycystic ovary syndrome - Ayman Shehata Dawood; Adel Elgergawy; Ahmed Elhalwagy (Wolters Kluwer Medknow Publications, 2018)
Objective: The objective of this study is to measure levels of Vitamin D3 and leptin and assess their relation of each to the pathogenesis of polycystic ovary syndrome (PCOS). Design: This was a cohort observational study. Settings: This study was conducted at the Department of Obstetrics and Gynecology, Tanta University. Materials and Methods: Ninety lean women were enrolled in this study and were allocated into two groups with 45 patients in each group: the first group (study group) who are lean women with PCOS and the second group (control group) who are the lean infertile patients without PCOS. Blood samples were collected and tested for study parameters. Results: There were no significant differences regarding demographic characteristics between both groups. The differences were in ovarian volume and hormonal profiles. Serum leptin was found to be significantly increased in lean PCOS than in control groups. Vitamin D3 levels were found to be lower in the lean PCOS group than in control group. Conclusion: Lean PCOS women are a unique group with specific hormonal profiles different from the typical PCOS profiles. Leptin and Vitamin D3 may have a role in the pathogenesis of lean PCOS, but large studies are still required regarding this unique group.